New furileusaurian remains from La Invernada (northern Patagonia, Argentina): A site of unusual abelisaurids abundance. (January 2022) - Méndez, Ariel H.; Gianechini, Federico A.; Paulina-Carabajal, Ariana; Filippi, Leonardo S.; Juárez-Valieri, Rubén D.; Cerda, Ignacio A.; Garrido, Alberto C.
Abstract: Two new specimens of abelisaurid theropods from La Invernada fossil area (Bajo de la Carpa Formation; Santonian) are described. They correspond to an incomplete skull and several postcranial remains. MAU-Pv-LI-582 (skull) shares some morphological traits with other furileusaurs ( Viavenator exxoni and Llukalkan aliocranianus ) from the same area, such as: presence of a rounded knob on the anteromedial border of the supratemporal fossa, large foramina for the caudal middle cerebral veins, and a triangular basisphenoid recess with Llukalkan, and a basituberal web ventrally concave, a large common foramen for the exit of CNs III and IV, and particularly the absence of a caudal tympanic recess with Viavenator . MAU-Pv-LI-665 (vertebrae and ribs) shares some features with Viavenator, such as the presence of a single pneumatic foramen in the mid cervical centrum, and the shape and orientation of the neural spine of the mid dorsal vertebra. These findings, added to the previous ones, not only reveal the abundance of abelisaurids in this geographical area, but also the variety of morphotypes that coexisted during the middle of the Upper Cretaceous, at least in the north of Argentine Patagonia.